(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present article intends to be a critical analysis of the socio-environmental responsibility concerning the biotechnological revolution, taking as a parameter the risk society - a term coined by Ulrick Beck to indicate the consequences or results of the industrial production and consumption model based on profit maximization. and development at any price. It is an exploratory study that made use of bibliographic, documentary, quantitative and qualitative research to analyze the regulation of medical-reproductive practice in Brazil, with the aim of linking Environmental Law regulations to the protection of life, in all its forms. It was demonstrated that the biotechnological revolution was responsible for redefining the threats to the genetic heritage, since medicine ended up merging with economic rationality and, consequently, moving away from ethics and law. It is certain that the responsibility of those who hire reproductive medical techniques can be weighed based on the socio-environmental impacts produced, and the establishment of minimum safeguards to protect human life is strictly speaking.